2014
DOI: 10.1016/j.jped.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Lower waist circumference in mildly-stunted adolescents is associated with elevated insulin concentration

Abstract: The results presented herein suggest that an increase in plasma insulin is one of the primary metabolic modifications in stunted individuals, and that this alteration could be identified at a lower WC cut-off point than in non-stunted counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Additionally, a recent study showed the presence of insulin resistance among Indian undernourished rural population that was improved after six months of food supplementation [66] . On the other hand, Clemente et al [67] observed higher serum insulin levels in stunted Brazilian children. These inconsistent findings could be due to different degree of malnutrition, ethnicity, age ranges of participants, pubertal stage, body weight status, as well as methods of biochemical analyses.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, a recent study showed the presence of insulin resistance among Indian undernourished rural population that was improved after six months of food supplementation [66] . On the other hand, Clemente et al [67] observed higher serum insulin levels in stunted Brazilian children. These inconsistent findings could be due to different degree of malnutrition, ethnicity, age ranges of participants, pubertal stage, body weight status, as well as methods of biochemical analyses.…”
Section: Discussionmentioning
confidence: 92%
“…Quando crianças foram avaliadas pelo parâmetro CC no Canadá e no Brasil, observou-se que o percentual de crianças que apresentaram CC elevada indicou aumento de risco cardiovascular em ambos os sexos, porém, foi mais prevalente no sexo masculino (19)(20)(21) . As médias de CC encontradas no presente estudo foram também significativamente superiores no sexo masculino, resultados similares ao encontrados por outros estudos (22,23) .…”
Section: Discussionunclassified